Arterial and venous peripheral vascular assessment using wearable electro-resistive morphic sensors - Varaki, Elham Shabani; Gargiulo, Gaetano D.; Malone, Matthew; Breen, Paul P. (Scientific reports, 2024)
Peripheral vascular diseases (PVDs) represent a significant burden on global human health and healthcare systems. With continued growth in obesity and diabetes, it is likely that the incidence of these conditions will increase. As many PVDs remain undiagnosed, low-cost and easy to use diagnostic methods are required. This work uses newly developed wearable electro-resistive morphic sensors to assess venous and arterial competence in the lower limbs of 36 healthy subjects. Comparison of this HeMo device was made to currently available benchtop light reflection rheography and photoplethymography devices. Results indicate that HeMo can detect the physiological signals of interest for both chronic venous insufficiency and peripheral arterial disease and all subjects were interpreted as healthy by each system. However, measurement repeatability of HeMo was highlighted as an issue that requires further system development. Furthermore, as HeMo captures changes in a section of limb circumference due to changes in underlying blood movement, rather than at a single point, the recorded signal is typically damped by comparison. This factor should be considered in any future developments.